MORPHOLOGY AND STATUS OF OCCURRENCE OF ANTHRACNOSE OF BEAN (PHASEOLUS VULGARIS L.) CAUSED BY COLLETOTRICHUM LINDEMUTHIANUM (SACC. AND MAGN.) SCRIB. IN KASHMIR VALLEY - JAN MOHD JUNAID; ARIF HUSSAIN BHAT, T. A. SHAH; N. A. BHAT; NISAR AHMAD DAR; V. K. AMBARDAR (The Bioscan, 2014)
Survey of important bean growing areas of Kashmir Valley was carried out to assess the disease incidence and intensity of anthracnose of beans. The disease was prevalent in all the potential bean growing pockets of the valley surveyed during the course of survey. The incidence ranged from 23.51% to 82.14% with disease intensity ranging from 8.75 to 33.38%. Highest disease incidence (34.81% and 51.11%) and intensity (13.73 and 21.91%) on leaves and pods was recorded in district Anantnag, with least in district Shopian (24.80% and 28.99%; 9.66% and 11.93%). The pathogen associated with the disease was isolated and identified as Colletotrichum lindemuthianum(Sacc and Magn.) Scrib. Morphological studies of the fungus revealed that conidia are hyaline, single celled dumbbell shaped born in acervuli bearing setae. The dimensions of the conidia on culture and host varied from 9.5-11.5 x 3.5-4.5(10.5x 4) and 12-22.0 x 4-6 (17.25 x 4.25), respectively. The fungus produces acervuli with its dimensions ranging from 140-320 (204.14) and 175- 285 (270) on culture and host respectively. It was also observed that the acervulibearing characteristic appendages on its surfaces that measure 64-108 x 2- 4 (84.22 x 3) and 60- 120 x 5-6 (90 x 5.55)on culture and host respectively.